RESISTANCE TO INNOVATION: ESSENCE, PREVENTIVE MEASURES AND WAYS OUT - V. I. Zagvyazinsky; T. A. Strokova (Russian State Vocational Pedagogical University, 2015)
The paper raises the issue of school teachers' resistance to innovations related to modernization procedures, updates of educational content, methods and forms. The rejection of innovations is regarded by the authors as a psychological and pedagogical phenomenon; its roots and causes being analyzed including the consequences of some ineffective, poorly developed and even harmful innovations introduced or proposed by the Russian Ministry of Education and Science. The research findings demonstrate different innovation barriers along with the resulting inner skepticism and its external manifestation. However, in spite of partially justified skepticism, the authors maintain that the firm resistance to any innovation adversely affects both the education quality and teachers' personal and professional characteristics. In conclusion, the paper suggests some preventive measures for overcoming teachers' resistance to positive innovations in educational practices, and describes a successful experience of one of the rural schools applying a psychological mechanism of internalization of innovations. Additionally, the role of the school principal in developing teachers' motivation for innovations is emphasized.